Valor nutricional da Brachiaria decumbens em três idades - Frederico Osorio Velasco (2011)
The aim of this work was to evaluate the nutritional value of Brachiaria decumbens grass. In the first experiment, we evaluated energy partition and enteric methane production in sheep fed Brachiaria decumbens grass harvested at 56, 84 and 112 days of re-growth. There was no difference between the treatments in the dry matter, gross energy and net energy intakes (P> 0.05) of the sheep. Increasing the plant age was observed a reduction in of digestible and metabolizable energy intakes of the sheep (P <0.05). There was a greater loss of gross energy in the faeces of sheep fed forage cut at 112 days of re-growth compared to the plant cut at 56 days (P <0.05). Greater energy losses in the form of urine and methane were observed in sheep receiving Brachiaria decumbens grass harvested with 56 days of re-growth compared to other treatments (P <0.05). There was no statistical difference for energy loss in the form of caloric increment of the sheep for the different treatments evaluated. There was no difference (P> 0.05) between the treatments for the energy use efficiency of sheep. There were no difference between the re-growth ages studied for net energy of Brachiaria decumbens grass (P> 0.05) and the mean value was 1.74 Mcal/kg DM. Sheep fed with B. decumbens grass harvested at 56 days of re-growth showed higher methane production (P <0.05) compared to the other treatments. There were no difference between the treatments evaluated (P> 0.05) for the animals O2 consumption and CO2 and heat production. It was observed a negative effect of the plant maturity on the ruminal fermentation kinetics measured by the semi-automated "in vitro" gas production technique and the degradability of the different nutritional components of the forage evaluated, the second and third experiments respectively. The grass cut with 56 days of re-growth showed higher cumulative gas production (P <0.05) and dry matter degradability (P> 0.05) compared to plant cut with 84 and 112 days of re-growth which did not show statistical difference (P> 0.05). With the advance of the B. decumbens grass maturity was observed a reduction in the maximum gas production potential, gas production rate and effective degradability of the dry matter with passage rates of 2.0% and 5.0%/h. The B. decumbens grass harvested at 56 days of re-growth showed highest dry matter, crude protein, neutral detergent fiber and acid detergent fiber degradability (P <0.05) when compared to the forage cut at 84 and 112 days of re-growth. Therefore, Brachiaria decumbens grass harvested at 56 days of re-growth has higher nutritional value compared to the grass cut at 84 and 112 days of re-growth